Ischemia Modified Albumin in Early Diagnosis of Acute Coronary Syndromes (Academia Journal of Medicine, 2021)
Background: Acute coronary syndromes (ACS) pose a diagnostic challenge in patients with unpredictable baseline ECGs or without evidence of myocardial necrosis. Its early diagnosis is of utmost importance as ACS has a high mortality. The present study was conducted to know the role of Ischemia Modified Albumin (IMA) as a Cardiac Marker in the early Diagnosis of ACS. Subjects and Methods: A cross-sectional study was conducted in 86 patients presenting with chest pain of less than 3hours. A 12-lead ECG was recorded, and a blood sample was taken for IMA and cardiac troponin T(cTnT). Results of all the parameters alone and in combination, were correlated with the final hospital diagnosis and analysed. Results: IMA was found to be abnormal among 72.1% of the patients. IMA had a sensitivity of 81.58% and a specificity of 83.33% which was found to be high when compared with other parameters. The combination of IMA, ECG, 2D ECHO, cTnT, and CKMB had a sensitivity of 100% and a specificity of 16.67%. Conclusion: The present study showed that IMA is a potential diagnostic biomarker for ACS. Further studies are required to support the present findings.
Keywords: Acute coronary syndromes; Ischemic Modified Albumin; Cardiac Marker